2022
DOI: 10.3390/children9091353
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Adolescent PKU Patients: Beyond Fat Mass

Abstract: There is a lack of evidence on the impact on body composition of high protein intake and types of protein substitutes in PKU patients—particularly in adolescents, who are more inclined to dietary transgressions. In this observational, cross-sectional study, PKU patients were observed during prepubertal age (p) or after the pubertal spurt (P), assessing body composition and bone quality and correlating these parameters with dietary compliance and types of protein substitutes. Anthropometric and dietary data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Indeed, avoiding supplement consumption at main meals may be attributed to their unpleasant odor and taste, eventually leading patients to associate their consumption with sugar-rich food. In this regard, several studies have reported an improved palatability of both GMP and/or LNAA as a way to promote a more regular supplement intake throughout the day [ 20 , 21 , 22 ]. In this study, intake habits reported by patients assuming GMP or LNAA did not differ from others, probably due to the small proportion of patients (3 out of 33) also using this formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, avoiding supplement consumption at main meals may be attributed to their unpleasant odor and taste, eventually leading patients to associate their consumption with sugar-rich food. In this regard, several studies have reported an improved palatability of both GMP and/or LNAA as a way to promote a more regular supplement intake throughout the day [ 20 , 21 , 22 ]. In this study, intake habits reported by patients assuming GMP or LNAA did not differ from others, probably due to the small proportion of patients (3 out of 33) also using this formulation.…”
Section: Discussionmentioning
confidence: 99%
“…So, the host dietary pattern will have a profound effect on the microbiota, favoring the growth of species that uses these fuel sources, and this diet-induced microbial structure will have a crucial impact on host physiology and disease process (Figure 4) [205]. There are some studies evaluating overweight and/or obesity prevalence in patients with PKU; this is mainly in pediatric patients [127,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230], but also in mixed pediatric and adult populations [182,191,[231][232][233][234] or only adults [181,[235][236][237][238] reporting different Nutrients can directly interact with microorganisms to promote or inhibit their growth, shaping the gut microbial community. Also, diet-derived antigens and compounds can shape the gut microbiota in an indirect fashion by affecting host metabolism and its immune system.…”
Section: Nutrition Therapy: How It Modulates Microbiota and Microbiom...mentioning
confidence: 99%
“…There are some studies evaluating overweight and/or obesity prevalence in patients with PKU; this is mainly in pediatric patients [127,[214][215][216][217][218][219][220][221][222][223][224][225][226][227][228][229][230], but also in mixed pediatric and adult populations [182,191,[231][232][233][234] or only adults [181,[235][236][237][238] reporting different results. This has been recently reviewed [1,239], and cardiovascular risk through MetS concerns not only increased body weight but also increased body fat and, more precisely, increased visceral and other ectopic fat deposition [59].…”
Section: Cardiometabolic Risk Factors In Patients With Pkumentioning
confidence: 99%
See 2 more Smart Citations